Alkyl chitosan film‐high strength, functional biomaterials. Issue 11 (14th August 2017) - Lu, Li; Xing, Cao; Xin, Shen; Shitao, Yu; Feng, Su; Shiwei, Liu; Fusheng, Liu; Congxia, Xie
Abstract: Biofilm with strong tensile strength is a topic item in the area of tissue engineering, medicine engineering, and so forth. Here we introduced an alkyl chitosan film with strong tensile strength and its possibility for an absorbable anticoagulation material in vivo was tested in the series of blood test, such as dynamic coagulation time, plasma recalcification time and hemolysis. Alkyl chitosan film was a better biomaterial than traditional chitosan film in the anticoagulation, tissue compatibility and cell compatibility. The unique trait of alkyl chitosan film may be for its greater contact angle and hydrophobicity ability to reduce the adsorption capacity for the blood component and the activity of fibrinolytic enzymes, enhance the antibacterial capacity than chitosan film. Moreover, none of chitosan film or butyl chitosan film exhibited quick inflammation or other disadvantage and degraded quickly by implanted test. Therefore, Alkyl chitosan film is of prospective properties as an implantable, absorbable agent for tissue heals, and this material need further research. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3034–3041, 2017.